Efeito da fotobiomodulação em diferentes parâmetros de irradiação no processo de reparo em modelo de tendinite induzida por colagenase em ratos - Silva, Romildo Torres da (2016)
Tendinopathies are inflammations in the tendon, usually frequent and difficult to treat. Low level laser therapy (LLLT) appears as promising treatment in the modulation of the repair process with no side effects. Objective: To study the effect of LLLT, comparing different wavelengths, energy and power in the repair process of the tendon. Material and Methods: Wistar rats were used after "animal ethics committee" approval. Tendinitis was induced by collagenase injection (100 μg diluted in 0.9% saline solution) on the calcaneus tendon of the rats. This work was divided in 3 phases: Phase 1: Determination of the time course in the mechanical properties variation and collagen quantification in 3,7,14,30,45,60 days and the gene expression of Tenascina-C, MMP3 and 13 in 2, 6,12, 24,48 and 72 hours. Phase 2: Comparison between 2 wavelengths (660nm and 830nm) with experimental groups: CTL (Healthy), and untreated tendinitis (NT) or treated with LLLT in 1 or 3J, and 100mW. Phase 3: Comparison of different powers at 830nm with the experimental groups: CTL, NT and laser 830 with 1J-50mW, 1J-100mW; 3J-50mW and 3J-100mW. The animals were euthanized and the calcaneus tendon was removed for analysis of mechanical properties and collagen quantification in 30 days and gene expression in 12 and 24 hours. Results: The NT group presented reduction of Fmax and increased deformation VS CTL and increased MMP3 and MMP13 expression. The irradiated group (830nm) showed better results in the mechanical properties and collagen proportion compared to the irradiated group (660nm). When using laser at 830nm, we observed improvement in the mechanical properties and the proportion of collagen I and III in the 3J-50mW and 1J-100mW groups compared to the other groups, as well as reduction of MMP3 and discrete increase of MMP13. The 1J-100mW group showed increased expression of Tenascin-C. Tendinitis reduced mechanical properties, also changes the collagen proportion. Both irradiated groups (660nm or 830nm) improved mechanical properties with maintenance on the collagen and reduction of MMP3 expression. The 3J groups in 50mW and 1J in 100mW presented the best results involving all analyzed performed. Conclusion: LLLT (830nm, 3J 50mW and 1J 100mW) promoted repair of the tendon improving the mechanical properties of the tendon and the proportion of collagen type I and III. The mechanism involved may be the modulation of MMP3 and 13 in addition to tenascin-C, related to the degradation and collagen fibers organization being both important in the inflammatory and remodeling phase in tendon.